Short-term exposure to ambient fine particulate matter and psoriasis: A time-series analysis in Beijing, China - Wu, Junhui; Chen, Hongbo; Yang, Ruotong; Yu, Huan; Shang, Shaomei; Hu, Yonghua (Frontiers in Public Health, 2022)
Background Ambient fine particulate matter (PM2.5) adversely affects human health and has been linked to a variety of skin disorders. However, little is known about the effects of PM2.5 on psoriasis. Methods The Beijing Medical Claim Data for Employees database recorded 500,266 outpatient visits for psoriasis during 2010–2017. A generalized additive quasi-Poisson model was used to examine the relationship between daily PM2.5 concentrations and outpatient visits for psoriasis with stratification by sex, age, and season. Results Short-term exposure to PM2.5 was associated with outpatient visits for psoriasis-related health concerns. A same-day increase of 10 μg/m3 in PM2.5 concentrations was associated with a 0.29% (95% confidence interval: 0.26–0.32%) increase in daily outpatient visits for psoriasis. Female and older patients appeared to be more sensitive to the effects of PM2.5 (P < 0.05). Conclusions Short-term elevations in PM2.5 concentrations may be associated with exacerbations in psoriasis. Further work is warranted to confirm the findings and elucidate the underlying biological mechanisms.